Recent advances in functional mesoporous silica-based nanoplatforms for combinational photo-chemotherapy of cancer. (February 2020) - Cheng, Yin-Jia; Hu, Jing-Jing; Qin, Si-Yong; Zhang, Ai-Qing; Zhang, Xian-Zheng
Abstract: In recent years, research trend has gradually removed from a concentration on monotherapy to combination therapy for fighting cancer. Combination photo-chemotherapy, including photodynamic-chemotherapy, photothermal-chemotherapy, as well as photodynamic-photothermal-chemotherapy, has demonstrated the priorities to elevate cancer therapeutic efficacies and diminish undesired side effects through different mechanisms in cancer treatment. In this review, we summarize the most recent progress in designing mesoporous silica-based nanoplatforms for combination delivery of multiple therapeutic agents, and discuss the treatment outcome in cancer by combining photodynamic therapy (PDT) and/or photothermal therapy (PTT) with chemotherapy. Furthermore, we highlight the drawbacks and challenges of employing mesoporous silica-based combinational formulations for effective cancer photo-chemotherapy, which might provide new guidelines for development of photo-chemo combination cancer treatments. Graphical abstract: Image 108765